Mediating Customer Satisfaction: Examining The Impact of Service Quality, Product Quality, and Price Perception on Consumer Loyalty at D’gunung Angkringan Malang - Iswari, Hanif Rani; Ainun, Siti Nur (Program Studi Manajemen, Fakultas Ekonomi dan Bisnis, Universitas Widya Gama, 2024)
This study explores the pivotal role of customer satisfaction as a key aspect of the business strategy, investigating its mediation among service quality, product quality, pricing, and customer loyalty at modern coffee shop D’Gunung Angkringan Malang. Modern coffee shop, a renowned local Indonesian brand, offers a diverse array of coffee beverages. Employing a quantitative descriptive approach and Structural Equation Modeling (SEM) analysis, this research examines the intricate interplay among service quality, product quality, pricing, customer satisfaction, and customer loyalty. With non-probability accidental sampling involving 50 respondents, regression analysis uncovers a significant direct correlation among the variables. Additionally, indirect effects highlight the substantial impact of the independent variables on customer loyalty, mediated by customer satisfaction. The findings underscore the importance of customer satisfaction in the coffee shop industry, crucial for retaining loyal customers. Notably, product quality, service, and pricing emerge as sensitive factors significantly contributing to customer satisfaction. Therefore, prioritizing attention to these aspects in coffee shop business can fortify customer loyalty and bolster overall business performance. This study provides valuable insights into consumer behavior dynamics within café settings, offering strategic implications for strengthening customer relations and improving business performance.